(3GdGMJQGa GdUMaj (B:s (3GdCSS h GdeJWdHGJ (B/s - (3YHGSI, LjdGdjs ((3GdLRGFQ (B:s (3OGQ gheI ,s, 2017)
(3jJfGhd GdcJGH HGdTQM h GdJaUjd afhf GdJMQjQ GdUMaj h bhGYO hCSS h eJWdHGJ hCNdGbjGJ GdeeGQSI GdGYdGejI GdJj dGHO Cf jYjgG GdUMaj LjOG MJi jchf HefCi Yf GdJLGhRGJ h jDOj GdegeI GdGYdGejI HGMJQGajI h caGAI h GbJOGQ (B.(3hbO Je GdJWQb Edi afhf GdJMQjQ GdUMaj GdeNJdaI ef GdLGfHjf GdfXQj h GdJWHjbj HWQjbI ejSQI h eQGMd GdJZWjI GdUMajI hCSS GdcJGHGJ GdUMajI GdLjOI h GdfGLMI h eJWdHGJ GdCOGA Gdegfj h GdVZhWGJ GdJj JhGLg GdUMaj (B, (3ceG jQcR GdcJGH Ydi GdOhQ GdPj jbhe Hg LgGR GdJMQjQ h Yed eNJda GdCbSGe GdeTcdI GgjFI GdJMQjQ h YedjGJ GdeJGHYI ddeGOI GdJMQjQjI NdGd eQhQgG YHQ GdbfhGJ GdeTcdI ddLgGR GdJMQjQj GfWdGbG ef GfLGRgG ef bHd GdUMaj Gdi ZGjI fTQgG Gdi LeghQ GdbQGA h ef LgI CNQi jJYQV GdcJGH Gdi GdeSDhdjI GdGLJeGYjI ddUMdajjf h CNdGbjGJ GdegfI h GdQbGHI GdJj jeGQSgG MQGS GdHhGHI h JCKjQgG Ydi GdCOGA Gdegfj ddGYdGejjf(B. s
Keywords: (3GdUMGaIs; (3GdUMaj GdeMJQas